2012
DOI: 10.1590/s0104-11692012000300020
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation of the Safety Attitudes Questionnaire - Short Form 2006 for Brazil

Abstract: The objective of this study was to perform a cross-cultural adaptation of the Safety Attitudes Questionnaire -Short Form 2006 for Brazil. The instrument was applied in six hospitals in three regions of Brazil. Content, face, and construct validity was performed. Analysis of the instrument's reliability was performed by verifying the items' internal consistency through Cronbach's alpha.The sample was composed of 1301 professionals working in clinical and surgical wards of six hospitals. Confirmatory analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
120
0
72

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(200 citation statements)
references
References 10 publications
8
120
0
72
Order By: Relevance
“…The scores can range from zero to 100 points, and means above 75 indicate the presence of attitudes favorable to patient safety. The reliability of the instrument has been satisfactory in previous studies (α = 0.65 to 0.79) (15) . The quality of the care provided in pediatric units was assessed by the following question posed to nursing professionals -"How do you assess the quality of nursing care provided to patients in your unit?…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…The scores can range from zero to 100 points, and means above 75 indicate the presence of attitudes favorable to patient safety. The reliability of the instrument has been satisfactory in previous studies (α = 0.65 to 0.79) (15) . The quality of the care provided in pediatric units was assessed by the following question posed to nursing professionals -"How do you assess the quality of nursing care provided to patients in your unit?…”
Section: Methodsmentioning
confidence: 58%
“…The instrument has satisfactory validity and reliability indexes (α = 0.65 to 0.91) (13)(14) . The presence of safety attitudes in the work environment was assessed using the Safety Attitudes Questionnaire -Short form 2006 (SAQ), validated to the Brazilian culture (15) . The SAQ contains 41 items and eight domains: teamwork climate, job satisfaction, safety climate, perceptions of management (unit and hospital), working conditions, stress recognition and safe behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Scores equal or superior to 75 points are considered as positive assessments of the safety climate and job satisfaction. (22) A Cronbach's alpha coefficient of 0.85 was found for the job satisfaction subscale and 0.77 for the safety climate subscale.…”
Section: Methodsmentioning
confidence: 93%
“…As highlighted, the instruments used have been adapted and validated for the Brazilian culture. (16,22) The data were organized in an electronic worksheet and the statistical software SAS® version 9.2. was used for the descriptive analysis of the sample. The absolute and percentage frequencies were assessed for the categorical variables and the position (mean, median, minimum and maximum) and dispersion measures (standard deviation) for the categorical variables.…”
Section: Methodsmentioning
confidence: 99%
“…CFA results for 2012 and 2013 data both revealed that the composite reliability of the scale exceeds the recommended .70 threshold and that the AVE estimates were above .50, providing evidence of convergent validity (Hair et al, 2006). Correlations Analysis and the square of interfactor correlations are reported in Table 5 and Management support contributes significantly to high levels of job satisfaction (Abdou and Saber, 2011;de Carvalho and Cassiani, 2012;Göras et al, 2013). Consequently, we suggest that attention to management system, work achievement, and promotion and evaluation should significantly improve job satisfaction.…”
Section: Confirmatory Factor Analysismentioning
confidence: 83%